Advocating for the inclusion of operatic collaborative piano curricula in higher education: Informing curricula through lived experience - Cupido, C. A.; van Zyl, S. (South African Journal of Higher Education, 2021)
The purpose of this article was to examine how the lived experiences of five professional collaborative pianists during the 35th International Hans Gabor Belvedere Singing Competition, that was held in Cape Town in 2016, could inform the inclusion of new curricula for specialised operatic collaborative piano modules in tertiary institutions. Based on the literature reviewed and themes that emerged from the data, a curriculum could include the following aspects: a knowledge of the rules of lyric diction in foreign languages; excellent sight-reading skills; knowledge of the art of orchestral reduction and repertoire; the ability to transcribe and reduce full opera scores. One personal skill that is not often developed and should also be included is the ability of a pianist to evince empathy when working with singers.